Produk dan Jasa Bank Syariah Dalam Kajian Literatur - sabri, sabri; Resti, Okfi (PT Kimshafi Alung Cipta, 2022)
In view of Islamic teachings, everything must be done neatly, correctly and regularly, the processes must be followed properly. Something should not be done carelessly. Islamic banks as a financial institution, one of its functions is to collect public funds, must have a source to raise funds before channeling them back to the community. The aim of the research is to find out whether the products and services of Islamic banks, fundraising products, financing products and other services are in accordance with existing theories. The research method used was a literature review. The results of this study explain that Islamic bank fund management is an effort made by Islamic bank institutions in managing or managing the position of funds received from funding activities to be channeled to financing activities which are the main source of bank income. In addition, bank services are banking activities carried out by a bank to facilitate the activities of raising funds and channeling funds. The conclusion of the research is that the more complete the bank services provided, the better the bank's operations will thus attract customers to make transactions and will increase the bank's income.